Sindrom Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) akibat Antibiotik: Laporan Kasus - SIti Maimunah; Meligasari L. Gaya (CV. Jasa Sukses Abadi, 2020)
DRESS syndrome is a severe drug adverse reaction characterized by skin eruption, fever, and involvement of internal organs. DRESS syndrome has a clinical manifestation similar to other allergic drug eruption. Establishing a diagnosis of DRESS Syndrome quickly and precisely becomes important so that appropriate treatment can be done to reduce the mortality rate due to DRESS Syndrome. This case report aims to show the diagnosis and treatment of cases of DRESS Syndrome in patients with 28-year-old female patients with a history of taking antibiotics. Reported a 28-year-old female patient came with complaints of reddish spots accompanied by itching in most of her body since 5 days ago, complaints accompanied by fever. Spots appear suspected after the patient took antibiotics, namely cefadroxil and amoxicillin after surgery to remove ovarian tumor. Based on physical examination and support, the diagnosis of Allergy Drug Eruption Syndrome type DRESS et causa is suspected of cefadroxil and amoxicillin. Medical management in the form of systemic corticosteroids, antihistamines, and topical corticosteroids. DRESS syndrome is one of the adverse drug reaction which is characterized by skin eruption, fever, and involvement of internal organs. Management of the main DRESS syndrome is the identification and stopping the drug that is suspected to be the cause, and recommended administration of systemic corticosteroids.